Practising social work ethics around the world : cases and commentaries - Banks, Sarah; Nohr, Kirsten (Routledge, 2012)
Ethics is an increasingly important theme in social work practice. Worldwide, social workers experience common ethical challenges (how to be fair, whether to break a rule, how to act in politically tense situations) in very different contexts - from disaster relief in China to child protection work in Palestine. This book takes as its starting point real life cases featuring ethical problems in the areas of: negotiating roles and boundaries, respecting rights, being fair, challenging and developing organisations and working with policy and politics. Each case opens with a brief introduction, is followed by two commentaries and ends with questions for reflection. The commentaries, written by authors from different countries, refer to relevant theories, concepts, practical matters, alternative courses of action and their implications.